2003
DOI: 10.1186/1471-2210-3-16
|View full text |Cite
|
Sign up to set email alerts
|

Protection against acute adriamycin-induced cardiotoxicity by garlic: Role of endogenous antioxidants and inhibition of TNF-α expression

Abstract: Background: Oxidative stress is the major etiopathological factor in adriamycin-induced cardiotoxicity. Relatively low amounts of endogenous antioxidant makes the heart vulnerable to oxidative stress-induced damage. Chronic oral administration of garlic has been reported to enhance the endogenous antioxidants of heart. We hypothesized that garlic-induced enhanced cardiac antioxidants may offer protection against acute adriamycin-induced cardiotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(20 citation statements)
references
References 29 publications
0
19
1
Order By: Relevance
“…Studies have confirmed that DOX-derived ROS could act as an intrinsic stress that activates mitogen activated protein kinases (MAPK), p38, JNK, and NF- κ B pathways as well as intracellular p53 accumulation, leading to an increase in proinflammatory cytokines (TNF- α and IL-1 β ) and alteration in the ratio of proapoptotic proteins to antiapoptotic proteins (e.g., Bax to Bcl-2), cytochrome C (Cyto C) release, and caspase-3 (C3) activation [2224]. The present study aims to investigate the potential anti-inflammation and antiapoptosis effect of hydrogen-rich saline on DOX-induced cardiotoxicity and hepatotoxicity in Wistar albino rats.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have confirmed that DOX-derived ROS could act as an intrinsic stress that activates mitogen activated protein kinases (MAPK), p38, JNK, and NF- κ B pathways as well as intracellular p53 accumulation, leading to an increase in proinflammatory cytokines (TNF- α and IL-1 β ) and alteration in the ratio of proapoptotic proteins to antiapoptotic proteins (e.g., Bax to Bcl-2), cytochrome C (Cyto C) release, and caspase-3 (C3) activation [2224]. The present study aims to investigate the potential anti-inflammation and antiapoptosis effect of hydrogen-rich saline on DOX-induced cardiotoxicity and hepatotoxicity in Wistar albino rats.…”
Section: Introductionmentioning
confidence: 99%
“…However, its practical therapeutic use is limited by the development of dose-dependent chronic cardiomyopathy [3, 4]. Previous studies on the mechanisms of ADR cardiotoxicity have reported that the formation of free reactive oxygen radicals [5, 6], release of cardiotoxic cytokines [7, 8], cytoskeletal changes [9] and intracellular calcium overload [10, 11] might be involved in the mechanisms of ADR cardiotoxicity. In our study, we found that ADR induces a higher rate of reactive oxygen species formation with depression of antioxidant enzyme activities and a decrease in total antioxidant capability.…”
Section: Discussionmentioning
confidence: 99%
“…Chronically, doxorubicin can increase TNF-α [47] and IL-1 [48] gene expression in rats. However, in this study myocardial TNF-α levels did not change after doxorubicin administration.…”
Section: Discussionmentioning
confidence: 99%